Análise cultural do torrão dos infernos: imaginário do mal nas poéticas de Dante Milano e Nauro Machado - Alexandre Fernandes Corrêa (Estudos de Literatura Brasileira Contemporânea)
This is an introduction to the cultural analysis of the imaginary of evil expressed in two works by Brazilian poets from different regions of the country. It is a com- parative study of the poetry of Dante Milano (RJ) and Nauro Machado (MA), through which we propose an archaeological excavation of the remains of the representation of evil in social and literary unconscious.